BORROWING TECHNIQUE IN THE TRANSLATION OF BALI LIVE MAGAZINE INTO INDONESIAN - I Wayan Suryasa (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2014)
This research was intended to describe the borrowing techniquesin the translation. The title of this research is Borrowing Technique in the Translation of Bali Live Magazine into Indonesian.The analysis focused on the borrowing techniques used to render foreign elements into Indonesian language in a printed advertisement.The data in this analysis were cited and grouped based on the borrowing techniques used to translate the source language into the target language using the borrowing technique proposed by Molina &Albir (2000:84). In this analysis, the borrowing technique used to translate the source language into the target language included two borrowing techniques, namely: (1) full absorption of words without any modification of pronunciation (pure borrowing), (2) the implementation of naturalized borrowing technique indicating a modification of pronunciation (referred to EYD).